First Report of Neofusicoccum mediterraneum and Neofusicoccum parvum Causing Pine Ghost Canker on Pinus spp. in Southern California - Bustamante, Marcelo I; Lynch, Shannon Colleen; Elfar, Karina; Kabashima, John N; Wood, Rhonda; Neault, Heather F; Rauhe, Madeleine B; Crain, Jeffrey; Lopez, Jasmine A; Penicks, Amanda; Mojica, Humberto; Atkinson, Mike D; et al. (Plant disease, 2023)
, and are important conifer species native to Mediterranean regions that are cultivated in the southwestern United States for landscaping (Phillips and Gladfelter, 1991; Chambel et al., 2013). Among them, Monterey pine ( ) is native to restricted areas of California and Mexico, but it is extensively grown for timber production in other countries, especially in the Southern Hemisphere (Rogers, 2004). From 2018 to 2022, severe dieback and cankers have been detected on more than 30 mature pines of the three species within a 40-ha urban forest in Orange County, Southern California. Symptoms initiate on the lower portion of the canopy and advance into the crown, leading to quick dieback and, in some cases, to tree death. Cross sections of affected branches revealed wedged cankers with irregular, indistinct margins, and cryptic discoloration (i.e., "ghost cankers"). Pycnidia were observed on the surface of each bark scale of branches with advanced infections. Two morphotypes of Botryosphaeriaceae colonies (n = 34 isolates) were recovered consistently from more than 90% of the symptomatic pines. Two isolates per morphotype were grown on pistachio leaf agar (Chen et al., 2014) for 14 days to induce pycnidia formation. Conidia (n = 50) were hyaline, thin-walled and fusoid to ellipsoidal in shape, ranging from 16.1 to 27.9 (22.6) × 5.4 to 8.2 (6.8) µm for the first morphotype and 11.5 to 20.4 (16.3) × 4.8 to 8.6 (6.3) µm for the second morphotype. The rDNA internal transcribed spacer (ITS), beta-tubulin ( ), and translation elongation factor 1-alpha ( ) partial gene regions were amplified and sequenced using the primers ITS5/ITS4 (White et al., 1990), Bt2a/Bt2b (Glass and Donaldson, 1995), and EF1-728F/EF1-986R (Carbone and Kohn, 1999), respectively. A multi-locus phylogenetic analysis revealed that isolates UCD9433 and UCD10439 clustered with the ex-type strain of (CBS:113083), and isolates UCD9161 and UCD9434 grouped with (CMW:9081). Sequences were submitted to GenBank (nos. OP535391 to OP535394 for ITS, OP561946 to OP561949 for , and OP561950 to OP561953 for ). Pathogenicity tests were performed with above-mentioned isolates on 20-mm-diameter healthy branches of mature Monterey pines (n = 10, 14 years old) located in a research field at UC Davis. Isolates were grown for 7 days on potato dextrose agar and inoculated in the internode area by removing a 5-mm-diameter disk of the bark with a sterile cork borer and placing a 5-mm-diameter mycelial plug. Controls were mock-inoculated with sterile agar plugs, and the experiment was performed twice. After three months, inoculations resulted in vascular lesions that ranged from 20.6 to 49.7 (32.7) mm with and from 13.5 to 71.0 (33.6) mm with , and the same pathogens were reisolated (70 to 100% recovery). Controls remained symptomless and no botryosphaeriaceous colonies were recovered. Both and are polyphagous pathogens associated with multiple woody plant hosts (Phillips et al., 2013). Previously, only has been associated with pine cankers in Iran, however, the pine species was not indicated (Abdollahzadeh et al., 2013). The detection of these pathogens in urban forests raises concerns of potential spillover events to other forest and agricultural hosts in Southern California. To our knowledge, this is the first report of and causing Pine Ghost Canker on , and .